The association between the interval of radioiodine treatment and treatment response, and side effects in patients with lung metastases from differentiated thyroid cancer - Wang, Hongxi; Shi, Lei; Huang, Rui; Liu, Bin; Tian, Rong (Frontiers in Endocrinology, 2023)
Objective: Repeated radioiodine (RAI) treatment has been widely implemented to RAI-avid and clinically respond lung metastatic differentiated thyroid cancer (DTC). We aim to investigate the association between the interval of RAI treatment and short-term response, side effect in patients with lung metastases from DTC, and to identify predictors for non-effective response to next RAI treatment. Methods: A total of 282 course pairs from 91 patients were established and categorized into two groups by the interval of neighboring RAI treatment (< 12 months and ≥12 months), and the characteristics and treatment response between the two groups were compared. Multivariate logistic regression was used to identify predictors associated with treatment response. The side effects at the former course and latter course were compared while taking into account the interval. Results: No significant difference was found between the two groups in treatment response at the latter course (P>0.05). In the multivariate analysis, age ≥ 55 years (OR=7.29, 95% CI=1.66-33.35, P=0.008), follicular thyroid cancer (OR=5.00, 95% CI=1.23-22.18, P=0.027), and a second RAI treatment as former course (OR=4.77, 95% CI=1.42-18.61, P=0.016) were significantly associated with a non-effective response. There was no significant difference in the side effects at the former and latter courses between the two groups (P>0.05). Conclusion: The interval of RAI treatment does not affect short-term response and side effects of DTC patients with RAI-avid lung metastases, it was feasible to defer repeat evaluation and treatment with an interval of at least 12 months to obtain an effective response and reduce the risk of side effects.